China-Russia Strategic Cooperation in Labour Development - I. V. Novikova (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2020)
Global competition requires innovation, which in turn is driven by a human factor. Labor resources are a prerequisite for the development of a country; therefore, a competition strategy for labor resources is becoming increasingly important for the development of enterprises or countries. With the deepening of global economic integration, thanks to political and geographical advantages and the possibility of increased political cohesion between China and Russia in terms of production factors, both sides are constantly strengthening cooperation. Labor cooperation is an important factor; labor shortages in the Russian Far East and Siberia may be closed by China’s labor resources. For the development of the northern regions of China, Northeast industrial cooperation with the Far East and Siberia is his top priority. For a more effective interaction between the two countries, a unified labor development strategy is necessary and are the basis of the economic resources of China and Russia.